An investigation into the quality of life improvements after vertebral osteomyelitis depending on the status of pathogen detection - Frank Beyer; Birte Wenk; Norma Jung; Jan Bredow; Peer Eysel; Ayla Yagdiran (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed to compare clinical characteristics and quality of life (QoL) after vertebral osteomyelitis (VO) based on the status of pathogen detection in microbiological sampling.